Game of Privilege : An African American History of Golf - Demas, Lane (Book collections on Project MUSE., 2017)
This groundbreaking history of African Americans and golf explores the role of race, class, and public space in golf course development, the stories of individual black golfers during the age of segregation, the legal battle to integrate public golf courses, and the little-known history of the United Golfers Association (UGA) - a black golf tour that operated from 1925 to 1975.